Edukasi Sistem Coretax kepada Karyawan PT Nariki Minex Sejati dalam Persiapan Laporan SPT Tahunan Orang Pribadi - Setyawati, Wiwit; Akhsani, Novi; Nurbaeti, Nurbaeti (Universitas Pamulang, 2025)
The digital transformation implemented by the Directorate General of Taxes through the Coretax Administration System introduces a new paradigm in tax administration, including the provision of pre-populated data for individual annual income tax returns. However, this innovation is not yet fully understood by taxpayers, including employees of PT Nariki Minex Sejati—a mining company with a large workforce. Initial surveys show that more than 75% of employees have never used Coretax and still rely on traditional reporting methods, creating risks of filing errors, data mismatches, and administrative sanctions. This community service program aims to enhance digital tax literacy, particularly understanding pre-populated data and developing the ability to use Coretax independently and accurately. The program was carried out through: (1) needs assessment via interviews, (2) socialization of tax literacy and introduction Coretax system, and (3) simulation of Coretax activation and initial use. Results indicate a 70% increase in participants’ understanding, and all participants successfully completed the activation simulation. In conclusion, strengthening digital tax literacy effectively improves taxpayers’ competencies in using modern tax administration systems. It is recommended that the program be continued through the development of a comprehensive guide for filing individual annual income tax returns and the provision of training materials to support self-directed learning. Keywords: Tax; Coretax, Annual tax return.